Moderators of the effectiveness of multisystemic therapy outcome for adolescents with severe conduct problems - Thanh Nam, Tran; Weiss, Bahr (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Adolescent conduct problems exact serious social as well as personal costs. One of the most effective programs for treatment of serious conduct problems in adolescents is multisystemic therapy (MST). Although research supports its effectiveness, relatively little is known about the conditions under which MST is most effective. The present study examined potential moderators of treatment outcomes in MST in 164 participants randomly assigned to receive MST or services as usual. A number of significant moderators were identified. Overall, adolescents from better functioning families benefitted more from MST than adolescents from less well functioning families, with 8 out of 10 significant moderators related to family or parent functioning supporting this position. Several hypotheses for this effect were proposed, including (I) that better functioning families may access useful resources more easily, (II) that in families with more cohesion and warmth adolescents may be less likely to automatically react negatively to parental limit setting behavior, and (III) that such families may have an adaptive rule structure in place already but not adaptive rule content. Received: 7th March 2016; Revised: 21st September 2016; Accepted: 5th October 2016